Innervated mouse pancreas organoids as an ex vivo model to study pancreatic neuropathy in pancreatic cancer - H. Erdinc Besikcioglu (Elsevier, 2021)
Summary: Pancreatic cancer is characterized by bi-directional interactions between pancreatic cancer cells and stromal cells including neural cells. The absence of neural cells in pancreatic organoids limits the investigation of cell- cell interaction and tumor innervation. This protocol describes how to generate innervated wild type (WT) and Kras+/LSLG12D Trp53fl/f lp48+/Cre (KPC) murine pancreatic organoids. To specifically investigate neurogenesis, organoids are co-cultured with iPSCs-derived neural crest cells, while co-culture with dorsal root ganglia explants is used for comparing organoids with mature neurons.For complete details on the use and execution of this protocol, please refer to Huch et al. (2013), Boj et al. (2015), and Demir et al. (2014).